(untitled) (Revista Direito em Debate, 2023)
This article, produced from ongoing research, aims to assess the deepening of the integration process of the Mercosur based on the development of a social dimension, parallel to its original economic dimension. It is questioned whether Mercosur, given the adoption of this social dimension, can be understood as another step in the multilevel system of protection of the human person. After examining the organic and administrative structure built to implement this social dimension, as well as analyzing the various actions and regulations aimed at protecting human rights, it was concluded that Mercosur is progressively consolidating as yet another level of protection for the individual. human rights in the regional bloc, together with the constitutional orders of the States Parties and Associates and the International Human Rights Law, created, in particular, by the Systems of the United Nations Organizations and the United Nations States. With the objective of projecting Mercosur with greater expression in this multilevel system of protection of the human person, the adoption of supranationality and the attribution of direct effect to norms emanating from supranational bodies were defended. The research carried out is exploratory with a deductive approach. As for the procedures, the research is bibliographical and documentary.